The separation wall effect of a volute twin entry cross section area on the mixed inflow turbine performance - Menaouar, Bencherif Mohammed (Array, 2021)
The pulse turbocharging system is used in many diesel engines and it is fortunate that nozzleless mixed turbines allow unsteady flow with less performance losses. It operates with a double or sometimes triple-entry casing creating different flow regimes in each sector. A nozzleless casing is used. The division of the cross section area takes the form of a solid wall in the radial plane. When the flow rate through one or the other volute inlet drops to zero, some reverse flow is observed from the other inlet. This situation suffers undesirable effects, diminishing the benefits of the divided volute casing types. A numerical investigation on the effect of the length of the dividing wall in the radial plane is performed using the ANSYS code. This possibility is explored and the results show that extending the wall to a limiting length enhances the flow behavior with better performance.